A COMPARISON OF THE HETEROGENEOUS NUCLEAR RNA OF HELA CELLS IN DIFFERENT PERIODS OF THE CELL GROWTH CYCLE - Pagoulatos, Gerassimos N. (The Rockefeller University Press, 1970)
HeLa cells synthesize heterogeneous nuclear RNA (HnRNA) in the G(1), S, and G(2) portions of the cell cycle. HnRNA prepared from these various periods was compared by RNA-DNA hybridization experiments. The results indicated that some of the HnRNA molecules were equivalent at all times in the cell cycle, but limitations in the sensitivity of the hydridization reactions, as well as in the spectrum of hybridizing molecules, restrict the conclusions that can be drawn from these comparisons.